CDF W mass anomaly revisited - Shou-hua Zhu (AAPPS Bulletin, 2023)
Abstract The CDF, ATLAS, and LHCb have released the measurements on the W boson mass $$m_W$$ m W at $$\sqrt{S}=1.96, 7, 13 TeV$$ S = 1.96 , 7 , 13 T e V , respectively. The measured values show the declining tendency, namely $$m_W$$ m W decreases with the increment of the collider energy. If the declining tendency is confirmed, it might be the signal of metric field at high-energy colliders. In this paper, we propose a model to account for such tendency and explore the properties of the model.